Answer:
x = -44/13
y = -65/13
Step-by-step explanation:
Using matrix form means using the crammers rule
The matrix form of the expression is written as;
[tex]\left[\begin{array}{ccc}8&5\\-1&1\\\end{array}\right] \left[\begin{array}{ccc}x\\y\\\end{array}\right] = \left[\begin{array}{ccc}9\\7\\\end{array}\right][/tex]
AX = B
taking the determinant of A;
|A| = 8(1) - 5(-1)
|A| = 8 + 5
|A| = 13
After replacing the first row with the column matrix;
[tex]A_x =\left[\begin{array}{ccc}9&5\\7&-1\\\end{array}\right][/tex]
|Ax| = 9(-1)-5(7)
||Ax| = -9 - 35
|Ax| = -44
x = |Ax|/|A|
x = -44/13
similarly for y
[tex]A_x =\left[\begin{array}{ccc}8&9\\-1&7\\\end{array}\right][/tex]
|Ay| = 8(7)+9
|Ay| = 56+9
|Ay| = 65
y = |Ay|/|A|
y = -65/13